Improvement of the Design phase by BIM to transform into a model-based AEC industry: A review of the relation between architects, contractors, and clients - Kiani Hashemiesfahani, Maryam; Skogh, Madeleine (My University, 2022)
Technology has changed a lot over the years, and there have been many positive advancements in the digital sector. As the digital sector is increasingly used in the construction sector, it is necessary that the technology develops at the same pace and adapts to the user's needs. In the construction industry, Building Information Modeling, and despite the evolution of BIM technology, its adoption is limited. The Architectural, Engineering, and Construction (AEC) industry are still mainly using its traditional ways of working, which means using 2D drawings instead of 3D models. This thesis studies what limits the construction industry from transforming from the traditional ways of using 2D drawings towards becoming entirely model-based in the design and construction. In addition, the relationship between architects, contractors, and clients has been investigated since the collaboration with the parties involved is essential to achieving the full implementation of BIM in the AEC industry. To understand the relationship between the parties involved and why BIM is not used more widely on the construction site, information management through BIM and how the information is shared and presented between them has been analyzed. The results of the thesis have been collected through eleven interviews with architects, engineers, and contractors. The results indicated that the most common way today is using and delivering a combination of 2D drawings and 3D models. It seems like producing 2D drawings, and 3D models require the same type of information, but despite this fact, architects put in a lot of effort and time to produce both. The results show many underlying factors to the limited transformation of becoming model-based. For instance, unclear demands from all involved parties, lack of knowledge, lack of frameworks and guidelines, unfriendly software, lack of trust in the BIM model, lack of supporting contracts, absence of open format, and the fact that the BIM model is not considered as a legal binding document.
Keywords: 2D drawings, 3D models, AEC industry, Architect, BIM implementation, BIM information, BIM model, Client, Contractor, Model-based production.